Correction: Nerdrum Aagaard et al. Significance of Neonatal Heart Rate in the Delivery Room-A Review. Children 2023, 10, 1551 - Ellisiv Nerdrum Aagaard; Anne Lee Solevåg; Ola Didrik Saugstad (MDPI AG, 2024)
In the original publication [...]